РАЗВИТИЕ ИДЕЙ "КОНСТРУКТИВНОЙ ГЕОГРАФИИ" В ГЕОМОРФОЛОГИИ - Лихачева Э.А.; Тимофеев Д.А. (My University, 2005)
Scientific-engineering line "constructive geography" suggested by LP. Gerassimov has involved the development of theory and methods of ecological and engineering geomorphology. "Constructive geography" and "constructive geomorphology" may serve as consolidating notion for different researches in the field "human and environment".